2022
DOI: 10.2196/39314
|View full text |Cite
|
Sign up to set email alerts
|

Dual Sensory Impairment as a Predictor of Loneliness and Isolation in Older Adults: National Cohort Study

Abstract: Background Loneliness and social isolation are global public health challenges. Sensory impairments (SIs) are highly prevalent among older adults but are often ignored as a part of normal aging. Identifying the role of SIs in loneliness and social isolation could provide insight into strategies for improving public health among older adults. Objective This study aims to analyze the effects of SIs on loneliness and social isolation among older adults in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Participants were considered to have DSI when both VI and HI were present. The evaluation and classification of sensory impairments were consistent with previous studies in CHARLS 24–26 …”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…Participants were considered to have DSI when both VI and HI were present. The evaluation and classification of sensory impairments were consistent with previous studies in CHARLS 24–26 …”
Section: Methodssupporting
confidence: 88%
“…Firstly, sensory impairments were selfreported by participants, and there may be selection bias. Although this method has been extensively used in similar studies [24][25][26] and there is evidence to suggest that self-evaluation of vision and hearing status may be more intuitive than clinical measurements. 50 Secondly, some unmeasured potential confounding factors were not included…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experience of multiple impairments is more than the sum of each impairment alone 8 . In that regard, combined vision and hearing loss, also known as dual sensory impairment, is associated with reduced social participation 17 and predicts social isolation and loneliness 18 …”
Section: Introductionmentioning
confidence: 99%
“…8 In that regard, combined vision and hearing loss, also known as dual sensory impairment, is associated with reduced social participation 17 and predicts social isolation and loneliness. 18 To date, only two cross-sectional studies have investigated the associations of tooth loss, vision, and hearing impairments with social participation among community-dwelling older adults. A study in Japan found that self-reported vision, hearing and tooth loss were associated with fewer social interactions with friends, after adjustment for sex, age, education, residence area, chronic conditions, and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%